A REVISED ORDOVICIAN AGE FOR THE MIRANDA DO DOURO ORTHOGNEISS, PORTUGAL. ZIRCON U-PB ION-MICROPROBE AND LA-ICPMS DATING - Bea F.; Montero P.; Talavera C.; Zinger T. (My University, 2006)
The Miranda do Douro orthogneiss was believed to be the oldest magmatic rock of the Central Iberian Zone, on the base of a U-Pb discordia upper intercept of 618 ± 9 Ma. Nevertheless, new ion-microprobe and LA-ICPMS U-Pb zircon dating revealed that the crystallization age was 483 ± 3 Ma. The orthogneiss also contains a 605 ± 13 Ma zircon population that indicates that the source-rock for the Ordovician magma was Pan-African. Moreover, a few ~3.17 Ga zircon grains were also recorded. These grains are the oldest found so far in Iberia, and its occurrence would suggest the involvement of an Archean crust in the Pan-African orogeny. © UB-ICTJA.
Keywords: CENTRAL IBERIAN ZONE; GNEISS; OLLO DE SAPO; PRE-VARISCAN; U-PB DATING; Archean; Ordovician; Precambrian::Archean; Докембрий::Архей; Paleozoic::Ordovician; Палеозой::Ордовикская